MASJID RAMAH ANAK DALAM PERSPEKTIF FIQH: masjid ramah anak - Dahlan, Syafii (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2024)
Mosques have an important role as centers of worship and education for Muslims. From a fiqh perspective, a mosque is not only a place for prayer, but also a space for social activities and learning for various groups, including children. However, in practice, children's involvement in mosques is often limited, even limited, due to concerns about disturbing the peace of worship. This paper aims to examine the concept of child-friendly mosques from a fiqh perspective and how mosques can be an environment that supports children's spiritual, social and intellectual development. Through a literature review method, this research highlights several opinions of ulama regarding the presence of children in mosques, including views that encourage their inclusion as a form of developing Islamic character from an early age. The results of the study show that child-friendly mosques not only allow children to participate in religious activities, but also provide them with a space to learn about etiquette and religious values. With the right approach, child-friendly mosques can serve as an important means of building a generation that understands and loves Islam from an early age.